Return to skills and urban size: Evidence from the skill requirements of Hungarian firms - László Czaller; Zoltán Hermann (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
While most empirical studies document that cognitive and social skills are strong predictors of individual earnings, their impact is not homogenous in space. We argue that dense urban settings utilize cognitive and social skills more intensively than rural areas, therefore the labour market return to these skills is higher in cities. Using data from a representative survey recording the skills requirements of Hungarian firms, we show that social skills are rewarded more in dense urban areas. Surprisingly, this pattern is not observed for cognitive skills. We use instrumental variables strategy to correct for measurement errors in skills, and to deal with the endogeneity of agglomeration. Our results are robust to alternative agglomeration measures and a large set of controls, however, returns to skills vary considerably across worker groups and industries.
Keywords: J24; J31; R12; 330; agglomeration; cognitive and social skills; wages; urban labour markets